Evolution characteristics of impact weather system and SST signals during years of anomalous Meiyu onset over the Yangtze-Huaihe River Basin - Jin, Xiaoxia; Ma, Yutong; Liu, Mei; Zhong, Shanshan (Frontiers in Earth Science, 2023)
On the basis of the Meiyu onset data from 1954 to 2020, the precipitation during the Meiyu Period, the NCEP/NCAR reanalysis data, the sea surface temperature data of NOAA, and the West Pacific subtropical high data provided by the National Climate Center, the climatic characteristics of Meiyu over the Yangtze-Huaihe River Basin and the primary impact system are investigated. Results indicate that the Meiyu onset date has an enormous interannual variation, t. The date of the earliest Meiyu emergence is 27 days prior to the latest. There is a strong relationship between the length of Meiyu and the rainfall. Meiyu's start is correlated with the northward motion of the South Asia High, the northward jump of the westerly jet, the northward jump of the subtropical high, and the northward motion of the low-level jet. In the early years of Meiyu, the northward jump of the aforementioned systems occurred earlier. In the early Meiyu onset years, the position of the westerly jet shifted from 34-35°N to 38-40°N, which is much further north than the typical climate position. From late May to early June, the subtropical high was extraordinarily powerful, the ridgeline reached 20°N, and the position was much to the north. In years with a late Meiyu onset, the position of the westerly jet and the ridgeline were further south than the climatological average from early to late June; the jump to the north was not evident until late June. In addition, the SST anomaly anomalies of the Indian Ocean and Pacific Ocean are significant external forcing variables that influence the Meiyu beginning date. The high SST of the equatorial Indian Ocean and the equatorial tropical eastern Pacific in the autumn of the preceding year, as well as the high SST of the equatorial Indian Ocean in the spring of that year, are all prophase indicators of an early Meiyu start in the Yangtze-Huaihe River Basin.